2017
DOI: 10.1515/folmed-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Mucocele of the Sphenoid Sinus

Abstract: Mucocele of the paranasal sinuses is a rare disease with slow evolution. It is a benign, encapsulated and destructive formation fi lled with mucous fl uid and tapistrated with respiratory epithelium. Of all the paranasal sinuses, the sphenoid sinus is aff ected in only 1-7% of the cases. We present two cases of mucocele of the sphenoid sinus involving the posterior ethmoidal cells. We consider here their clinical presentation, use of neuroimaging in the diagnosis, surgical care and postoperative results. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Headaches caused by sphenoid sinus mucoceles occur primarily in the retrobulbar position in the early stages15 and are usually bilateral and progressive. Discomfort caused by the mucocele can be relieved by the administration of nonsteroidal anti-inflammatory drugs 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Headaches caused by sphenoid sinus mucoceles occur primarily in the retrobulbar position in the early stages15 and are usually bilateral and progressive. Discomfort caused by the mucocele can be relieved by the administration of nonsteroidal anti-inflammatory drugs 16.…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysical examination found that 4 patients presented with oculomotor nerve palsy, 4 patients had optic nerve or abducens nerve palsy, and 1 patient had optic neuropathy, oculomotor nerve palsy, and abducens nerve palsy simultaneously. 14 Headaches caused by sphenoid sinus mucoceles occur primarily in the retrobulbar position in the early stages 15 and are usually bilateral and progressive. Discomfort caused by the mucocele can be relieved by the administration of nonsteroidal antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Uncommon, but serious, complications include meningitis, brain abscess, orbital cellulitis, orbital abscess, and mucocele (10). A mucocele is a benign, but potentially destructive, mucus-containing cyst that can form in any of the sinuses and may present with a progressive headache and cranial nerve palsies due to compression, especially in the sphenoid sinus (55,56).…”
Section: Rhinosinusitismentioning
confidence: 99%
“…A recent systematic review showed that the occurrence rate of orthognathic surgery was 38.1% in individuals with bilateral cleft lip and palate (BCLP), 30.2% for unilateral cleft lip and palate (UCLP) 4.4% for isolated cleft palate (ICP), and 1.8% for patients with isolated cleft lip (ICL), after the orofacial cleft repair [12]. The identification of SS'pneumatization in individuals with and without CLP is important to avoid complications in surgical procedures, including hemorrhages, sinus infections, formation of mucoceles and can be from a surgical approach with inadequate planning [8,13]. Also, infections can occur for the intracranial region, representing a higher risk for the individual, such as: subdural abscess; extradural abscess; brain abscess; meningitis; thrombophlebitis or osteomyelitis [14].…”
Section: Introductionmentioning
confidence: 99%